Implementation of Solar-Powered Water Purification Technology to Enhance Quality of Life in Rural Areas - Suyitno, Suyitno; Arifin, Zainal; Tjahyana, Dominicus Danardono Dwi Prija; Juwana, Wibawa Endra; Rachmanto, Rendy Adhi; Yaningsih, Indri (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2024)
This study presents the development and implementation of a solar-powered reverse osmosis (RO) water purification system at Pondok Pesantren Tijarotul Qur’aniyah, Sub-district of Bulu, District of Sukoharjo, Indonesia. The project aimed to provide a sustainable solution to the urgent need for clean drinking water in the community. The implementation process was divided into four main phases: comprehensive survey and needs analysis, prototype development and testing, system implementation, and long-term monitoring and evaluation. The initial survey identified significant issues with water quality and accessibility, leading to the design of a tailored RO system powered by solar energy. The prototype was rigorously tested and adjusted based on user feedback to ensure it met community requirements. The system was implemented on a small scale, involving the construction of necessary infrastructure and integration of solar panels for reliable power. Post-implementation water quality tests showed substantial improvements in key parameters. Results included a pH level of 7.20, hardness (CaCO₃) at 252.87 mg/L, total dissolved solids (TDS) at 0.023 mg/L, and iron (Fe) at 0.2639 mg/L. Chlorine and chromium levels were 0.00 mg/L, manganese (Mn) was 0.1001 mg/L, ammonia (NH₃) was 1.14 mg/L, and sulfate (SO₄) was 11.26 mg/L. All parameters met the quality standards set by the Indonesian Ministry of Health and Government Regulation on Water Quality Management. Continuous monitoring and educational programs were incorporated to ensure local engagement and long-term sustainability. This study demonstrates that the solar-powered RO system effectively meets the community’s need for clean water and offers a scalable model for similar regions, highlighting the potential of combining renewable energy with advanced water purification technologies. Keywords: Water Purification, Reverse Osmosis, Solar Energy, Water Quality, Sustainability